Risk, Protection, Provision and Policy - Freeman, Claire; Tranter, Paul; Skelton, Tracey (Geographies of Children and Young People ;, 2017)
The volume provides an overview of recent research (within geography and allied disciplines) around the overarching concept of 'safe and accessible places of encounter'. It develops according to three interrelated themes. The first part of the volume examines several of the many spaces children use and that are relevant to the geographies of children and young people including: the city centre and inner city high rise housing, urban versus suburban and rural spaces, local neighbourhoods, the 'home' (for particular groups of children and young people such as child domestic workers in Bangladesh), school playgrounds, services (such as domestic violence shelters), outdoor natural spaces, and "life space" (where music and arts are presented in a non-political space in Bosnia-Herzegovina). The second part examines how notions of safety, protection and risk relate to providing children and young people with good life chances, and accessible spaces that enhance or reduce well-being. This middle section emphasises the debate about risk and the need to balance risk and safety/protection. The final part focuses on policy that builds on the provision/identification of spaces, safety/protection and risk. The emphasis is on how policy at different levels (international-national-local-family) helps provide better spaces of encounter and enhances life chances for children and young people. This section also recognises the different levels of policy making associated with different parts of the world and different regional settings. The gap between policy intentions and outcomes is recognised (e.g Cambodia's policies on orphanage tourism). The policy section includes contributions that relate to planning, education, migration, architecture, health, connection and citizenship, and sustainability. It provides insights into how professionals working in these fields can, through policy, enhance children's and young people's lived experiences and living environments.p>.